Research on Students’ Representations about Professional Success: Emotions and Values - Nazarenko Natalia (Insight: the psychological dimensions of society, 2023)
The purpose of the research is to identify dominant valuesin students’ representations about professional success;determine correlations of the emotions of joy, angerand fear with the values of professional success of studentsfrom Ukraine. Methods: a survey conducted by meansof the method “Identification of an individual’s life values”or “Must-test” (Ivanov, Kolobova, 1992); the method forexamining personal emotional features (Olshannikova,Rabinovich, 1974) was used to establish the levelof an individual’s inclination toward experiencing the threebasic emotions: fear, anger and joy. The obtained datawere analyzed using descriptive statistics and the Pearsoncorrelation coefficient. Results. It was found that dignity(19.84%), personal development (14.51%) and taking careof others (8.21%) are dominant values in the students’ representations. The findings confirmed a significantpositive correlation between the emotions of angerand fear and the identified value categories: dignity, takingcare of others, safety and financial security. It was foundthat all the value categories of students have a statisticallysignificant correlation except the category of recognitionwhich has no significant correlation with other valuesof the respondents. It was established that the categoryof dignity has a positive correlation with taking careof others that is the only category which has a significantcorrelation with the category war theme. A negativesignificant correlation between the emotion of joyand the value category of recognition was determined.Discussion and сonclusions. It was proved that dignity,personal development and taking care of others aredominant values in the students’ representations aboutprofessional success. It was found that the categoryof recognition has the lowest index 1.16% in the students’representations about professional success. Statisticallysignificant correlations between the emotions of anger,fear and joy and the value categories of the students’representations were substantiated.